BUILDING STRUCTURAL AWARENESS THROUGH SPIRITUAL LEADERSHIP: A CASE STUDY IN THE EDUCATIONAL ENVIRONMENT - Arifin, Samsul; Rizquha, Ach (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze how spiritual leadership is implemented at MAN 1 Bondowoso and its impact on structural awareness among students and staff. Spiritual leadership, which emphasizes values such as honesty, justice, and compassion, is applied by the principal in daily management as well as in various religious and social activities. This study uses a qualitative approach with a case study method, involving participatory observation, in-depth interviews, and document analysis. The results of the research show that the implementation of spiritual leadership at MAN 1 Bondowoso has successfully increased social awareness, environmental consciousness, and attention to the academic needs of students. Programs such as community service, school greening, and personal academic guidance have become integral parts of the school culture. Despite challenges such as resistance from some parties, solutions through ongoing training and socialization have proven effective. In conclusion, spiritual leadership at MAN 1 Bondowoso has significantly built structural awareness. The application of spiritual values in school leadership creates a more caring, inclusive, and welfare-oriented environment. Continuous commitment and support from the entire school community are needed to overcome challenges and sustain these positive impacts.